Independent Smallholders' Perceptions towards MSPO Certification in Sabah, Malaysia - Mohd Hafizuddin-Syah Bangun Abdullah; Shahida Shahimi; Amran Arifin (Institut Pertanian Bogor (IPB University), 2022)
In a wake of concern towards sustainable palm oil products, the Malaysian government had continuously formulated various guidelines for palm oil industries in fulfilling the international sustainability requirement. In 2013, Malaysia has launched Malaysian sustainable palm oil (MSPO), which eventually become mandatory requirement in January 2020, including the independent smallholders. However, the numbers of independent smallholders that acquired MSPO was relatively low, stood at 30.66%. Therefore, this study aims to analyse the perceptions of independent smallholders towards MSPO in Malaysia. A structured questionnaire was used for data collection instrument that been distributed among 350 independent smallholders, with a response rate of 74.5%. Results from descriptive analysis showed that independent smallholders have a good perception towards MSPO certification. Furthermore, multiple regression analysis revealed that all three factors were significant to influence the perceptions, where the risk perception became the most important contributor. This study enhances the awareness of sustainability practices among independent smallholders and contributes to the implementation of MSPO certification. Since risk perception has emerged as the primary contributor, regulators or governing bodies must seriously consider risk mitigation concerning independent smallholders about risk exposure such as continuous monitoring to comply environment impact assessment requirement, improve the availability and accessibility of information and aggressive awareness campaign on MSPO.